Petrographic study of a building deteriorated due to alkali-silica reaction, in Buenos Aires city (Argentina) - Marfil, Silvina Andrea (2008)
The columns of a building from 1935, located in Buenos Aires city, show cracks that have put the whole structure at risk. A petrographic study was carried out in order to determine the origin of concrete deterioration. The macroscopic characteristics and the reaction products developed in the cracks and in the reaction rims on the deleterious aggregates were analysed. In the selected material, X-ray diffraction and scanning electron microscopy and energy dispersive spectroscopy (SEM-EDS) were also used to determine the mineralogy. The deleterious reactions that affect the concrete obliterate the mortar texture. Most of the coarse aggregates develop reaction processes with the precipitation of a low birefringence material, but without peripheral concentric cracks. It is concluded that the structure has been deteriorated by the development of the alkali-silica reaction. The reactivity is clearly related to the coarse aggregate, especially to siliceous sandstones with a cryptocrystalline silica matrix and particles composed of different types of metastable silica such as chalcedony and agate.